2007
DOI: 10.1007/s10773-006-9325-7
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy of Resonances: Branch Point and Branch Cuts in Parameter Space

Abstract: The rich phenomenology of crossings and anticrossings of energies and widths, observed in an isolated doublet of resonances when one control parameter is varied, is fully explained in terms of the topological properties of the energy hypersurfaces close to the degeneracy point. The hypersurface representing the complex resonance eigenvalues, as functions of the control parameters, has an algebraic branch point of rank one, and branch cuts in its real and imaginary parts, in parameter space. Associated with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a companion paper (Hernández et al, 2007), we argued that, when discussing the mixing properties of an isolated doublet of unbound states, it is convenient to write the S−matrix poles, k 1 , and k 2 , in terms of a pole position function k 1,2 as…”
Section: Sections Of the Energy Hypersurfacementioning
confidence: 99%
See 1 more Smart Citation
“…In a companion paper (Hernández et al, 2007), we argued that, when discussing the mixing properties of an isolated doublet of unbound states, it is convenient to write the S−matrix poles, k 1 , and k 2 , in terms of a pole position function k 1,2 as…”
Section: Sections Of the Energy Hypersurfacementioning
confidence: 99%
“…In Hernández et al (2007), it was shown that the functions K(d, V 3 ) and k 2 1,2 (d, V 3 ) are regular functions of the parameter (d, V 3 ) at the exceptional point (d * , V * 3 ) and may be expanded in a Taylor series about this point. Hence…”
Section: Sections Of the Energy Hypersurfacementioning
confidence: 99%
“…Some of the earliest examples of EPDs have been also observed in structures with spatial periodicity which are explored, for instance, in [13][14][15][16], such as those exhibiting degenerate band edges or stationary inflection points. Although EPDs are usually viewed from a linear algebra standpoint, and are associated with systems described by matrices with Jordan blocks [1,13], it has been observed that they also represent points in configuration space where multiple branches of spectra connect, and are linked to branch points in the space of control variables [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed account of these and other results will be published elsewhere [22,23] V. SUMMARY AND CONCLUSIONS…”
Section: R E Immentioning
confidence: 87%